2024
DOI: 10.1002/adma.202309183
|View full text |Cite
|
Sign up to set email alerts
|

Analogous Design of a Microlayered Silicon Oxide‐Based Electrode to the General Electrode Structure for Thin‐Film Lithium‐Ion Batteries

Jong Heon Kim,
Aeran Song,
Ji‐Min Park
et al.

Abstract: Development of miniaturized thin‐film lithium‐ion batteries (TF‐LIBs) using vacuum deposition techniques are crucial for low‐scale applications, but addressing low energy density remains a challenge. In this work, we designed structures analogous to SiOx‐based thin‐film electrodes with close resemblance to traditional LIB slurry formulations including active material, conductive agent, and binder. The thin‐film was produced using mid‐frequency (MF) sputtering with a single hybrid target consisting of SiOx nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, the disadvantages of the Si anode are low electrical conductivity and large volume changes on cycling, which leads to fast capacity fading and a poor cycle life [6][7][8]. Many studies have reported techniques for preparing silicon/carbon (Si/C) composites with different graphite or carbon precursors, which is an effective approach to suppress the severe capacity degradation of pure Si [9][10][11][12]. While Si is dispersed into the carbonaceous matrix, the Si/C composite can buffer the large volume expansion of Si and improve its conductivity [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the disadvantages of the Si anode are low electrical conductivity and large volume changes on cycling, which leads to fast capacity fading and a poor cycle life [6][7][8]. Many studies have reported techniques for preparing silicon/carbon (Si/C) composites with different graphite or carbon precursors, which is an effective approach to suppress the severe capacity degradation of pure Si [9][10][11][12]. While Si is dispersed into the carbonaceous matrix, the Si/C composite can buffer the large volume expansion of Si and improve its conductivity [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%